Improvement of alum & PACL coagulants for the treatment of pulp and paper mill wastewater - Ambikapathi, A. Vishnushama (2010)
The wastewater arising from pulp and paper mills is highly polluted and has to be treated before discharged into rivers.Coagulation –flocculation process is a widely used water and wastewater treatment method.This method is used in pulp and paper mills to remove the suspended solids in the wastewater produced from the production processes.This study is aimed to provide a clear understanding of the effects of pH,settling time,and coagulant dosage towards the removal of pollutants in the wastewater.Also,it is aimed to improve the removal of pollutants by adding Fenugreek mucilage.The experiments were done using jar tests. Settling times were set to 30, 60, 90, and 120 minutes.The pH values were adjusted to 3, 6, and 9.Aluminium Sulphate (Alum), Polyaluminium Chloride (PACl) and Fenugreek mucilage dosages were manipulated at the values 50, 100, 500, 1000, 1500, and 2000 mg/L.The treated wastewater samples were tested for BOD, turbidity, and COD.The results showed the optimum pH for the research was 6,the optimum settling time was 30 minutes, and the optimum dosages of alum, PACl, and Fenugreek mucilage were 1000, 500, and 500 mg/L respectively.Through the research,it was deduced that Fenugreek mucilage improves pollutant removal when used with alum or PACl.